Employment and Wages in 2017: A Good Year for Aboriginals and Non-Aboriginals in Canada - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2018)
Employment, unemployment and wage rates improved for Aboriginals and non-Aboriginals in Canada in 2017. Participation rates remained the same for Aboriginals and slightly increased for non-Aboriginals. All four of these rates, employment, unemployment, participation and wages, are currently and historically more favourable for non-Aboriginals than for Aboriginals. However, when examined by the educational level completed, wage and employment rates are similar. Measures of employment are examined by gender, age, province, economic sector, and education, and for Métis, First Nations and Inuit.